Strategi Peningkatan Promosi Usaha UMKM Kota Pangkalpinang Memanfaatkan Artificial Intelligence: Pengabdian - Seno Hadi Saputro; Jhon Hendri; Sudirman Sudirman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program (PKM) aims to enhance the capacity of Small and Medium Enterprises (UMKM) entrepreneurs in Pangkalpinang City to utilize digital technology and artificial intelligence (AI) for product promotion. Through the Participatory Action Research (PAR) method, ten UMKM entrepreneurs were trained in blog creation and the use of AI for marketing content. The results demonstrate significant improvement in digital competence, with all participants successfully creating UMKM blogs containing a minimum of five product contents. This study provides tangible contributions to digital transformation of local SMEs and expands their market reach.